2018
DOI: 10.1007/s11356-018-2666-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E alleviates phoxim-induced toxic effects on intestinal oxidative stress, barrier function, and morphological changes in rats

Abstract: Phoxim is an organic phosphorus pesticide that remains easily in the environment, such as human food and animal feed. The objective of this study was to explore the effect of vitamin E on phoxim-induced oxidative stress in the intestinal tissues of Sprague-Dawley (SD) rats. Forty-eight Sprague-Dawley rats were randomly assigned to a control group and three treatment groups: treatment group 1 (phoxim: 20 mg/kg·BW), treatment group 2 (phoxim: 180 mg/kg·BW), and treatment 3 (vitamin E + phoxim: 200 mg/kg·BW + 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Vitamin E (alpha- and gamma-tocopherol) supplementation was reported to mitigate colitis, as well as protect the intestinal barrier function in mice by inhibiting colitis-induced loss of the tight junction protein occludin, and mitigates TNF-α/IFN-γ-induced impairment of trans-epithelial electrical resistance in human intestinal epithelial Caco-2 cell monolayer ( 37 ). In addition, supplementing vitamin E reduces phoxim (organophosphate pesticides) toxicity in rat intestinal tissues by alleviating phoxim-induced toxic effects on the intestinal oxidative stress, barrier function, and morphological changes ( 38 ). Furthermore, a study by Cadir et al ( 39 ) showed that the supplementation of omeprazole and/or vitamin E exerts protective effects on the biochemical and histopathological intestinal damage induced by hypoxia/reoxygenation in newborn rats ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E (alpha- and gamma-tocopherol) supplementation was reported to mitigate colitis, as well as protect the intestinal barrier function in mice by inhibiting colitis-induced loss of the tight junction protein occludin, and mitigates TNF-α/IFN-γ-induced impairment of trans-epithelial electrical resistance in human intestinal epithelial Caco-2 cell monolayer ( 37 ). In addition, supplementing vitamin E reduces phoxim (organophosphate pesticides) toxicity in rat intestinal tissues by alleviating phoxim-induced toxic effects on the intestinal oxidative stress, barrier function, and morphological changes ( 38 ). Furthermore, a study by Cadir et al ( 39 ) showed that the supplementation of omeprazole and/or vitamin E exerts protective effects on the biochemical and histopathological intestinal damage induced by hypoxia/reoxygenation in newborn rats ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main function of vitamin E is its natural antioxidant capacity, α-tocopherol having the greatest potency [7,8]. In this sense, it has been described that vitamin E administration reduces TNFα production in rats treated with a pesticide [30], as well as increasing occludin expression and decreasing NFκB expression in the intestine of rats exposed to a high altitude hypoxia environment [31]. Therefore, these results suggest that tiger nut could be effective in intestinal inflammatory processes.…”
Section: Discussionmentioning
confidence: 87%
“…The structural integrity of the intestine guarantees functional tness for digestion, a fundamental process for nutrient absorption (Sun et al 2018). This process requires the presence of the intestinal microbiota, which is related to the stress response and can be affected even by pesticides (Gao et al 2018).…”
Section: Discussionmentioning
confidence: 99%